Diagnósticos, resultados e intervenções de enfermagem relacionados ao comportamento sexual da pessoa idosa - Nóbrega, Thainar Machado de Araújo (2018)
Introduction: Among the aspects that have affected the lives of the elderly people, we can highlight the maintenance of sexual activity, generating demands of care for health services and skilled professionals to promote a comprehensive care, with improvement in their quality of life, welfare and autonomy. In order to enable Nursing to meet this clientele, from the perspective of sexuality, one should use the nursing process and its practice/diagnostic/results/interventions elements, providing the elderly person with a comprehensive care. Objective: To draw up Nursing Assertions of Diagnoses, Outcomes and Interventions related to the sexual behavior of the elderly person. Method: This is a methodological research, based on the Brazilian method for the development of terminological subsets of CIPE®, which was developed in three steps: 1) Identification of terms relevant to the clinical practice of nursing regarding the sexual behavior of the elderly person, from 22 scientific papers about the topic; 2) Cross-mapping of the terms identified with the terms of CIPE® version 2017 and validation of terms by experts, validating those that obtained a degree of agreement greater than or equal to 80%; 3) Drawing up, from identified and mapped terms, nursing assertions of diagnoses/ outcomes /interventions, as well as validation by experts, validating those that obtained a degree of agreement greater than or equal to 80%. The research was approved by the Research Ethics Committee under opinion nº 2.096.793 and CAAE: 67126517.0.0000.5188. Results: We identified a total of 533 terms in the pertinent literature, of which 377 are included in CIPE® version 2017. We drew up 111 diagnoses/ outcomes were, of which 101 were validated by experts, and 466 nursing interventions. Of the 101 diagnoses/ outcomes, 43 were classified into Psychobiological Needs, 57 into Psycho-social Needs and 1 into Psycho-spiritual Needs, according to Horta’s theory. Final Considerations: We believe that the assertions of diagnoses/outcomes and interventions drew up and based on Horta’s theory may underpin the clinical practice of nursing, thus easing up communication among nurses in the context of the sexual behavior of the elderly person, with a view to focusing the sexual health of this population.